The Long-Term Impact of Maternal Anxiety and Depression Postpartum and in Early Childhood on Child and Paternal Mental Health at 11–12 Years Follow-Up - Walker, Annika L.; Peters, Priya H.; de Rooij, Susanne R.; Henrichs, Jens; Witteveen, Anke B.; Verhoeven, Corine J. M.; Vrijkotte, Tanja G. M.; de Jonge, Ank (Frontiers in Psychiatry, 2020)
Background Postpartum maternal anxiety and depression can affect child development and family functioning. However, the long-term impact of postpartum maternal anxiety and depression on child and paternal mental health is understudied. The present large-scale prospective cohort study is one of the first to investigate whether maternal anxiety and depressive symptoms postpartum and at child age 5–6 years separately and synergistically increase paternal anxiety and depressive symptoms and child emotional problems in early adolescence at age 11–12 years. Secondly, we investigated whether concurrent paternal anxiety and depressive symptoms at child age 11–12 years moderated the association between maternal anxiety and depressive symptoms in the postpartum period and at child age 5–6 years with child emotional problems at age 11–12 years. Methods This study is part of the Amsterdam Born Children and Development (ABCD) cohort study, the Netherlands (N = 2.298). Maternal postpartum anxiety and depressive symptoms were assessed using the State-Trait Anxiety Inventory (STAI) and the Center for Epidemiologic Studies Depression Scale (CES-D) at 13 weeks postpartum. Maternal anxiety and depressive symptoms at child age 5–6 years and parental anxiety and depressive symptoms at 11–12 years were assessed using the Depression Anxiety Stress Scale (DASS-21). Child emotional problems were reported by the child and a teacher using the Strengths and Difficulties Questionnaire (SDQ). Multivariable linear regression was conducted, adjusted for demographic, perinatal/obstetric confounders, and affective symptoms of the other family members at 11–12 years. Results Neither maternal anxiety nor depressive symptoms were related to paternal depressive symptoms at child age 11–12 years, while maternal postpartum depressive symptoms, depressive symptoms at 5–6 years and maternal anxiety at 5–6 years were positively related to paternal anxiety at 11–12 years. However, effect sizes were small. Only maternal postpartum depression was positively but weakly associated with more child emotional problems at 11–12 years. Although paternal concurrent affective symptoms were positively related to more child emotional problems in early adolescence, they did not moderate the association between maternal symptoms and child emotional problems. Conclusions Our results indicate that fathers and children seem to be affected only to a small extent by maternal postpartum anxiety or depression.